Water and Sanitation Submission to the UAE – Belém work programme on indicators for measuring progress achieved towards the targets of the UAE Framework for Global Climate Resilience - Alliance for Global Water Adaptation; Alliance for Water Stewardship; French Water Partnership; Simavi; International Water Management Institute; German Federal Ministry for Economic Cooperation and Development; Gesellschaft für Internationale Zusammenarbeit (2024)
The Glasgow–Sharm el-Sheikh work programme COP 28 decision’s on the global goal on adaptation (GGA) included the launching of a two-year UAE – Belém work programme on indicators for measuring progress achieved towards the targets established in paragraphs 9 and 10 of the Decision, with a view to identifying and, as needed, developing indicators and potential quantified elements for those targets. At the same time, Parties and Observers were invited to submit, via the United Nations Framework Convention on Climate Change (UNFCCC) submission’s portal, by March 31st 2024 views on the development of indicators and quantified elements for the GGA targets, as well as views on modalities of the UAE – Belém work programme (e.g. organization of work, timelines, inputs, outputs and the involvement of stakeholders). This submission by United Nations Water (UN-Water) has been coordinated by UNICEF and the Sanitation and Water for All (SWA) Partnership. UN-Water is the coordination mechanism on water and sanitation, within the UN-system, bringing together the knowledge and experience of over 30 UN entities and over 40 partners. The joint submission ensures that the views of many different constituencies beyond the UN-System have been captured as it has gone through a wide set of parallel consultations: